VD_FINDINFO Jug / 2016 / 108 vom 4. November 2015 - VD Tribunal cantonal (2015)
RETRAITVOIE DE DROIT, RECOURS JOINT, SUPPRESSIONEN GÉNÉRAL, INDEMNITÉEN GÉNÉRAL | 135 CPP (CH), 386 al. 2 CPP (CH), 401 al. 3 CPP (CH)